The study of incidence of prostate cancer in transurethral resection of the prostate (TURP) specimens - Kongsanoon, Siripong; Lerdpraiwan, Weelak (Insight Urology, 2019)
Objective: To study the incidence of prostate cancer in TURP specimens in Phramongkutklao Hospital. Material and Method: A retrospective database included TURP specimens (2008-2016) in Phramongkutklao Hospital. The pathologic reports from 1,494 patients were investigated. There were 293 patients who did not meet the inclusion criteria. The cohorts were categorized into 2 groups according to age: men < 65 years (254 patients) and > 65 years (1001 patients). Result: According to the final pathological report for TURP specimens, BPH was detected in1203 specimens (95.9%) BPH and prostate cancer in 51 specimens (4.1%). In men < 65years with cancer, tumors were identified in 3.9% of specimens (T1a=10%, T1b=90%), and in men > 65 years in 4.1 % of specimens (T1a=22.5%, T1b=77.5%). Following the diagnosis in men < 65years with cancer: 1/10 radical prostatectomy, 1/10 RT only, 3/10 ADT+RT, 5/10 ADT only and 1/10 brachytherapy. In men > 65 years with cancer, treatments were classified: 3/41 observation, 3/41 active surveillance, 1/41 RT only, 10/41 ADT+RT, 21/41 ADT only and 2/41 brachytherapy. Conclusion: The incidence of incidental findings of prostate cancer in TURP is not uncommon in older patients. Our results suggest that careful investigations should be undertaken before surgery. In addition, prostatic specimens from TURP are essential and should be sent for pathological examination. Undiagnosed cancer may result from other procedures without tissue specimens, such as PVP, and finally loss of specimen for pathological examination.